PEMBARUAN HUKUM ISLAM DALAM TERAPAN DAN PERUNDANG-UNDANGAN DI INDONESIA - Asriati, Asriati (DIKTUM: Jurnal Syariah dan Hukum, 2012)
Based on the IMPRES No. 1 of 1991 dated June 10, 1991 jo. Ministerial Decision of Religious Affairs No. 154 of 1991 Date July 22, 1991, Islamic Law Applies nationally and where possible be used as guidelines and implemented by community and religious court judges throughout Indonesia. In setting decisions, the judges based on the Compilation of Islamic Law. Given the changes and reforms brought by KHI will require an analysis of the nuances and established Islamic law reforms contained therein, including that on the registration of marriages and permits polygamy. The idea of renewal of Islamic law in Indonesia has basically been pioneered in a long time and it happens among Muslims own relatively intense pull between the traditionalists / conservatives are so attached to the School of schools of jurisprudence on the one hand and the modernists who break away from the bonds schools of fiqh on the other. The traditional jurist does not require the registration of marriages, while in KHI recording it is a necessity and the marriage is not registered in the view does not have the force of law. Permit polygamy according to traditional Islamic law strictly without reservations may even allow polygamy are less likely to be responsible, while in KHI polygamy is seen as an emergency exit and skill must be with the permission of the court and the conditions are stringent. The foundation of the constitutional ideal and KHI is the Pancasila and the 1945 Constitution. It's a presidential decree published in the preamble and in the general explanation KHI. It was conceived as part of the national legal system that ensures the survival of religion based on belief in the Almighty God who simultaneously embodies the legal awareness and Indonesia. This is in accordance with article 29 paragraph 1 of the 1945 Constitution